(untitled) (Research, Society and Development, 2023)
There are many changes in everyday life during a process of illness and hospitalization. Cancer carries with it ideas related to finitude that sometimes require elaboration, knowledge and care. Educational technologies are available as a tool for health promotion and continuing education in patient care. In this way, the objective of the study was to produce an educational and informative booklet about palliative care for cancer patients in palliative care, their families and caregivers. It was a research of the methodological development type with a qualitative approach, referring to investigations of the methods of obtaining and organizing data and conducting research. The product developed was a booklet entitled “Palliative Care: Ways to care”, consisting of 22 topics about general palliative care. The booklet created through accessible content could contribute to the development and expansion of knowledge on the subject, for patients, caregivers and all those who have access to the prepared material. In addition, the booklet was presented as a possibility, or guiding thread, for dialogue on the theme and its personal and social crossings.